Purification and Oxidation Studies of Multiwall Carbon Nanotubes using Raman Spectroscopy - Hussain, Shahir; Islam, S.S.; Islam, T. (Asian Journal of Chemistry, 2011)
A process of chemical purification of multiwall carbon nanotubes (MWNTs) is investigated to determine the structural and chemical changes in atomic bond caused by chemical treatment. As-grown multiwall carbon nanotubes were treated in mixture of H2SO4, HNO3 under a refluxing condenser with magnetic stir for different time period 5, 7, 9 and 15 h (samples S1, S2, S3 and S4, respectively) at 70 ºC in order to remove amorphous carbon and catalysts completely. The acid-treated tubes are extensively characterized by means of Raman spectroscopy. Raman spectra were recorded for as-grown as well as post treated multiwall carbon nanotubes samples as prepared for different time duration. The results of Raman spectroscopy suggest that the appropriate mixing ratio between H2SO4 and HNO3 is 3:1 with treatment time from 5-9 h is suitable for purification and create less defect during acid treatment.